2010
DOI: 10.1075/aila.23.03tyl
|View full text |Cite
|
Sign up to set email alerts
|

Applying cognitive linguistics to instructed L2 learning

Abstract: This paper reports the results of a quasi-experimental effects-of-instruction study examining the efficacy of applying a Cognitive Linguistic (CL) approach to L2 learning of the semantics of English modals. In spite of their frequency in typical input, modal verbs present L2 learners with difficulties, party due to their inherent complexity — modals typically have two divergent senses — a root1 sense and an epistemic sense. ELT textbooks and most grammar books aimed at L2 teachers present the two meanings as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The results of the present study demonstrated that the metaphor awareness-raising approach group outperformed the non-cognitive approach and control groups in the writing, comparison, and categorization tests, and the self- and teacher-directed approach groups performed similarly within either the cognitive (the SC and TC) or the non-cognitive (the SN and TN) approach domains on the online computer program. These results revealed that the proximal–distal metaphor awareness-raising approach helps to remember expressions of certainty, thereby lending support to findings in previous studies (Berendi et al, 2008; Boers, 2000; Tyler et al, 2010, 2012) on the effects of the metaphor awareness-raising approach. All of the previous studies utilized metaphors embedded in target expressions or included in the concrete meanings of the target expressions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the present study demonstrated that the metaphor awareness-raising approach group outperformed the non-cognitive approach and control groups in the writing, comparison, and categorization tests, and the self- and teacher-directed approach groups performed similarly within either the cognitive (the SC and TC) or the non-cognitive (the SN and TN) approach domains on the online computer program. These results revealed that the proximal–distal metaphor awareness-raising approach helps to remember expressions of certainty, thereby lending support to findings in previous studies (Berendi et al, 2008; Boers, 2000; Tyler et al, 2010, 2012) on the effects of the metaphor awareness-raising approach. All of the previous studies utilized metaphors embedded in target expressions or included in the concrete meanings of the target expressions.…”
Section: Discussionsupporting
confidence: 89%
“…Comparing the teacher-directed metaphor awareness-raising approach with the traditional teaching approach, Tyler, Mueller, and Ho (2010) explored the efficacy of the teacher-directed metaphor awareness-raising approach in teaching English modals to learners of English as a foreign language (EFL) in a US university, and found more improvement for the metaphor awareness-raising approach group than for the traditional group. Furthermore, Tyler, Mueller, and Ho (2012) also demonstrated that the teacher-directed metaphor awareness-raising approach proved better than the traditional approach for teaching the semantics of the English prepositions to, for , and at to Vietnamese EFL learners.…”
Section: Applying Cognitive Linguistics As a Pedagogical Approachmentioning
confidence: 99%
“…They produced detailed theoretical CL descriptions of English prepositions (Tyler & Evans, 2003), phrasal verbs (Mahpeykar & Tyler, 2015), and modality (Tyler & Jan, 2017). They also applied their CL descriptive materials in empirical studies of L2 instruction on English prepositions (Tyler et al, 2011), modal verbs (Tyler et al, 2010), and conditionals (Jacobsen, 2018). These studies tended to adopt task-based language teaching (TBLT) as the instructional framework.…”
Section: Schematic Diagrams and Second Language Pedagogymentioning
confidence: 99%
“…Li 2009, study 5) or where the CL group devoted more time to the lexical items that would be the object of the post-test (e.g. Tyler, Mueller & Ho 2010).…”
Section: Does It Work?mentioning
confidence: 99%
“…While the CL groups outperformed the comparison groups to a statistically significant degree, this was probably due to the poor performance of the latter. For example, in Tyler et al's (2010) study (on modal verbs), the students who had received the CL-inspired instruction gained on average just 2.6 out of 32 test items between pre- and post-test. The comparison group made no progress.…”
Section: Does It Work?mentioning
confidence: 99%